2020
DOI: 10.3390/nano10061158
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interfacial Phase and π–π Stacking in Aligned Carbon Nanotube/Polyimide Nanocomposites

Abstract: To characterize the interfacial microstructure and interaction at a nanoscale has a significant meaning for the interface improvement of the nanocomposites. In this study, the interfacial microstructure and features of aligned multiwalled carbon nanotube (MWNT) and conjugated polymer polyimide (PI) with three molecular structures were investigated using small-angle X-ray scattering (SAXS), wide-angle X-ray diffraction (WAXD), and fluorescence emission spectroscopy. It was found that aligned MWNT/PI nanocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…This peak can also be the result of parallel stacking of carbon tube layers. It has been shown that peak (002) intensity decreases in aligned CNTs [39]. The distance between the carbon nanotube plates and the type of nanotube formation can affect the (002) peak [36].…”
Section: A Characterizationmentioning
confidence: 99%
“…This peak can also be the result of parallel stacking of carbon tube layers. It has been shown that peak (002) intensity decreases in aligned CNTs [39]. The distance between the carbon nanotube plates and the type of nanotube formation can affect the (002) peak [36].…”
Section: A Characterizationmentioning
confidence: 99%
“…Generally, two-, three- and multidimensional molecular network can be organized based on types of monomer linking (covalently, coordinating and/or supramolecular), where can indicate such as: covalent organic frameworks (COF) [ 5 , 6 ], coordination polymers [ 7 ], metal-organic frameworks (MOF) [ 8 ] and supramolecular polymers [ 9 , 10 , 11 ]. Supramolecular structures are self-assembled small molecules held together by reversible noncovalent interactions, such as hydrogen bonds [ 12 , 13 ], coordination [ 14 ], π–π stacking [ 15 , 16 ], and host-guest interactions [ 17 , 18 ], etc. It is noteworthy that supramolecular polymers do not comply with classical Carothers’ definition of a polymer as a single macromolecule but rather the idea of polymers as colloidal aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The normally used method to extract the fractal feature of packaging materials is to employ the material micromorphology in the preparation process, surface, or fracture morphology of packaging material, and the test data in the property change process of packaging material (e.g., acoustic emission (AE) signal [ 18 ]) to carry out image gray processing and noise reduction processing, respectively. Common methods for calculating fractal dimension include the box counting method [ 19 ], correlation dimension method [ 20 ], Hurst index method [ 21 ], slit island method [ 22 ], yard stick method [ 23 ], area-perimeter method [ 24 ], Sierpiński carpet method [ 25 ], semi-variance method [ 26 ], and power spectral density [ 27 ] (PSD) method. The main methods to obtain object image are scanning electron microscope [ 28 ] (SEM), transmission electron microscope [ 29 ] (TEM), atomic force microscope [ 30 ] (AFM), and other imaging techniques.…”
Section: Basic Theory Of Fractalmentioning
confidence: 99%